Analisis Pengukuran Kinerja Proses Manajemen Koperasi Menggunakan Indikator Balanced Scorecard - Novia Silviani; Rendra Trisyanto S (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Koperasi Pegawai Pemerintah Kota Bandung (KPKB) implements a process management performance measurement system from a financial perspective only. This measurement is considered to have several drawbacks. The purpose of this study is to determine the performance of the Koperasi Pegawai Pemerintah Kota Bandung using a balanced scorecard. The Balanced Scorecard is a comprehensive measurement method that includes four perspectives, namely: finance, customers / members, internal business processes and learning and growth. This research was conducted by taking data during 2019. The type of research used is descriptive qualitative research with a case study approach. The results of measurements carried out at the Koperasi Pegawai Pemerintah Kota Bandung using the balanced scorecard indicator, obtained an overall score of 87.68, which is a contribution from a financial perspective score of 36.81, a member perspective 16.64, an internal business process perspective 19, and a learning and growth 15.23. The overall score of 87.68 shows that the performance of the Koperasi Pegawai Pemerintah Kota Bandung is very good.